PERBAIKAN TEGANGAN PADA JARINGAN TEGANGAN MENENGAH 20 KV PENYULANG TOMAT GARDU INDUK MARIANA SUMATERA SELATAN: Budi Santoso, Albert Gifson, Dicky Pratama - Jurnal, Redaksi Tim (ENERGI & KELISTRIKAN, 2018)
In power systems, particularly in medium voltage 20 kV feeder that are its length exceeds 100 kms the same thing is found in many tissues PT. PLN (Persero) outside Java island for example in South Sumatra in feeder Tomat Mariana substation 105,094 kms in length and threshold voltage feeder receive Tomat at 16,397 kV. According to the standards established by SPLN: 72 of 1987 in the amount of 5% to JTM with radial configuration in this paper will discuss what steps need to be done to correct the voltage at the feeder Tomat Mariana substation with the help of ETAP 12.6.0 application using methods repair replacement Conductor , installation of capacitors and transformers Tap settings.